Zahraničný obchod ekonomiky SR v procese tranzície - Farkašovská, Mária (Univerzita Pardubice, 2001)
According to conservative economists it is possible to consider the transformation process for finished, when the liberalization of prices are finished and the institutional frame of functioning market economy is formed. Macro economy analysis and economy politics in the field of structural adaptive processes are willing to admit them, only at the level of sector structural economy. Even this reality, that the transitive countries with their sector structural economy came near do developed market economies, is often used as argument, that the transformation is done in the field of reconstructuralization of economy. It is necessary to emphasize that this sector movement to sector of services has been do no with non standard methods e.g. without adequate raise of work productivity, especially in industry. This is reason, why the reached sector structure does not correspond with the one, in transitive countries as economy level of gross national on an inhabitant.These facts show, that the most important sector in the Slovat republic on the way to reach the level of EU countries, is industry. The sector movement in conditions of transformation is necessary,but not the only condition of permanent growth of economy to follow the level of EU coutries. Another condition is important, structural production changes in processing innovation, the change to production of more dynamic segment in international business. As mentioned above,a very imporant goal of economy transformation should be structural adaptation of industry and important change of small economically developed economies.This should be the country on its way prepared for entry in EU.
Keywords: Slovensko; Ekonomika; Zahraniční obchod; restrukturalizace